2021
DOI: 10.1007/s10653-021-00974-3
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) in soils of an industrial area in semi-arid Uzbekistan: spatial distribution, relationship with trace metals and risk assessment

Abstract: The concentrations, composition patterns, transport and fate of PAHs in semi-arid and arid soils such as in Central Asia are not well known. Such knowledge is required to manage the risk posed by these toxic chemicals to humans and ecosystems in these regions. To fill this knowledge gap, we determined the concentrations of 21 parent PAHs, 4,5-methylenephenanthrene, 6 alkylated PAHs, and biphenyl in soils from 11 sampling locations (0–10, 10–20 cm soil depths) along a 20-km transect downwind from the Almalyk me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…These three farms are located less than 2 km from the steel industry and less than 5 km from the zinc industry. Similar enrichment in heavy-molecular-weighted PAHs has been previously reported in soils located less than 2 km from a Cu smelting industry [ 37 ]. These results suggest that livestock near industrial areas may be exposed to above-threshold levels of several pollutants when they feed on forage cultivated on local soils.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These three farms are located less than 2 km from the steel industry and less than 5 km from the zinc industry. Similar enrichment in heavy-molecular-weighted PAHs has been previously reported in soils located less than 2 km from a Cu smelting industry [ 37 ]. These results suggest that livestock near industrial areas may be exposed to above-threshold levels of several pollutants when they feed on forage cultivated on local soils.…”
Section: Resultssupporting
confidence: 84%
“…In the third principal component, a remarkable association was observed among high concentrations of PAHs, Zn, and Cd, consistent with emissions from the Zn smelting industry [ 32 ]. The correlation between Zn and heavy molecular-weighted PAHs has been also observed in soils near Cu smelting industries [ 37 ]. The high levels of PAHs and the contribution of Pb in the third component, together with the absence of PAHs in the other two components, may indicate heavy-traffic pollution as another source [ 39 ].…”
Section: Resultsmentioning
confidence: 98%
“…It is known that environmental exposure is one of the main sources of human exposure to PAHs. A recent study reported that in the soils of an industrial area in semi-arid Uzbekistan, PAH derivative (MPAHs and OPAH) levels were lower than those of their corresponding parent PAHs [ 36 ]. Another study showed that the concentrations of the OPAHs in the atmospheric particle phase were lower than their corresponding PAHs [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations, composition patterns and transport of chemicals and POPs in soil are highly complex (Bandowe et al 2021), which makes them some of the most harmful sources of contamination and environmental pollution. For instance, PAh are resistant to environmental degradation due to their highly hydrophobic nature (Gan et al 2009) and their widespread introduction to the environment through motor vehicle exhausts (Morillo et al 2007).…”
Section: Introductionmentioning
confidence: 99%